Vibrational resonances and Cu B displacement controlled by proton motion in cytochrome c oxidase - Farantos, Stavros C.; Guallar, Victor; Varotsis, Constantinos; Daskalakis, Vangelis (My University, 2010)
Cytochrome c oxidase (CcO), found in the inner mitochondrial membranes or in many bacteria, catalyzes the four-electron reduction of molecular oxygen to water. Four protons are pumped across the inner mitochondrial membrane through CcO. In this study, quantum mechanics/molecular mechanics and molecular dynamics calculations are used to probe the spectroscopic characteristics of the ferryl intermediates in the aa 3 CcO/O 2 reaction. These highly elaborate calculations, supported by several calculations on smaller model systems, demonstrate the sensitivity of vibrational frequencies on the Coulombic field of heme a 3 and their dependence on the distance of the adjacent Cu B to the heme a 3-Fe atom. This distance seems to be associated with the protonation state of the heme a 3 propionate A, and we propose that it plays a crucial role on the mechanism of action of CcO. In detail, we link proton pumping activity in CcO enzyme (a) to a multiple (1:1:2) resonance among the frequencies of FeIV=O bond stretching, the breathing mode of Histidine 411, and a bending mode of the His411-FeIV=O species (aa 3 from Paracoccus denitrificans numbering) and (b) to Cu B displacement by electrostatic interactions toward the heme a 3 iron. We find that the vibrations of the His411-FeIV=O unit become highly coupled depending on the protonation state of the heme a 3 ring A propionate/Asp399 pair, and we propose a mechanism for the resonance Raman enhancement of the bending mode δ(His411-FeIV=O). Calculations on model systems demonstrate that the position of Cu B in relation to heme a 3 iron-oxo plays a crucial role in regulating that resonance. We also discuss the origin of the coupling between bending, δ(His411- FeIV=O) and v(Fe=O) stretching modes, and the role played by such vibrational coupling interactions or CuB position in controlling functional properties of the enzyme, including electron/proton coupling as well as experimental spectra
Keywords: Electron Transport Complex IV; Heme; Heme a3